Hypertrophic cardiomyopathy: insights into pathophysiology and novel therapeutic strategies from clinical studies - Samuel Oluwadare Olalekan; Olalekan Olanrewaju Bakare; Patrick Godwin Okwute; Ifabunmi Oduyemi Osonuga; Muinat Moronke Adeyanju; Victoria Biola Edema (The Egyptian Heart Journal)
Abstract Background Hypertrophic cardiomyopathy (HCM) is a frequently encountered cardiac condition worldwide, often inherited, and characterized by intricate phenotypic and genetic manifestations. The natural progression of HCM is diverse, largely due to mutations in the contractile and relaxation proteins of the heart. These mutations disrupt the normal structure and functioning of the heart muscle, particularly affecting genes that encode proteins involved in the contraction and relaxation of cardiac muscle. Main body This review focused on understanding the role of contractile and relaxation proteins in the pathogenesis of hypertrophic cardiomyopathy. Mutations in contractile proteins such as myosin, actin, tropomyosin, and troponin are associated with hypercontractility and increased sensitivity of the heart muscle, leading to HCM. Additionally, impaired relaxation of the heart muscle, linked to abnormalities in proteins like phospholamban, sarcolipin, titin, myosin binding protein-C, and calsequestrin, contributes significantly to the disease. The review also explored the impact of targeted therapeutic approaches aimed at modulating these proteins to improve patient outcomes. Recent advances in therapeutic strategies, including novel pharmacological agents like mavacamten and aficamten, were examined for their potential to help patients manage the disease and lead more accommodating lifestyles. Conclusions The review underscored the significance of early diagnosis and personalized treatment approaches in managing HCM. Future research should prioritize the development of robust biomarkers for early detection and risk stratification, particularly in diverse populations, to enhance clinical outcomes. Furthermore, it is imperative to delve deeper into the genetic mutations and molecular mechanisms associated with HCM, with a focus on exploring the roles of less-studied myocardial relaxation proteins and their interactions with sarcomere constituents.